A Review Of Processing At The Cannington Ag/Pb/Zn Mine (The Southern African Institute of Mining and Metallurgy, 2007)
Commissioning of the Cannington processing plant began in October 1997. The nameplate capacity (of 1.55 million tonnes of ore per annum) was achieved relatively quickly. Since then (like many mines) the operation has strived to increase throughput and improve valuable metal recoveries, to offset declining head grades and lift the value of the operation. The processing plant now has the capability of treating over 3.2 million tonnes of ore per annum and in financial year 2005/06 the combined concentrate production exceeded 600 000 wet tonnes, approximately 80 per cent above concentrate output in the first full year of operation (at the design feed rate). This improved performance was achieved by making changes and additions to each of the major unit processes - primary grinding, flotation, leaching, filtering and paste fill preparation. The changes have included: adding a fines flotation circuit, expanding the grinding circuit, adding a pebble crusher, switching from continuous to batch leaching, building paste conveyors and decommissioning the column flotation cleaning circuits. This paper reviews these changes, outlines the current operating practices and discusses the challenges or opportunities that remain.